Literature Review: Faktor-Faktor Yang Berhubungan Dengan Status Gizi Pada Remaja - Ade Ifah Latifah; Anisa Fitria; Irfa Nur Fauziah (LPPM STIKes BHAKTI HUSADA CIKARANG, 2026)
Adolescents' nutritional status is one of the seventeen Sustainable Development Goals (SDGs) that must be met by 2030. In addition to Indonesia's growing adolescent population, the topic of adolescent nutrition demands particular study because of its impact on both adult nutritional issues and physical growth and development. Numerous intricate and interrelated causative factors contribute to the rise of dietary problems among adolescents. To create nutritional programs that are appropriate and effective for the target demographic, a thorough understanding of these elements is essential. The purpose of this study is to ascertain how maternal education, physical activity, body image, nutritional awareness, and other elements pertaining to adolescent nutritional status are related. This research employs a literature review to elaborate on theories, findings, and other research materials obtained from reference sources that will serve as the foundation for further research activities. The independent variables in this study are nutritional knowledge, maternal education, physical activity, body image, and other factors, while the dependent variable is adolescent nutritional status. The literature review of six journals indicates that determinants of adolescent nutritional status can lead to variations in the nutritional status of individual adolescents. Adolescent nutritional knowledge was not found to be related to adolescent nutritional status. Maternal education and body image showed a relationship with adolescent nutritional status. Other factors related to adolescent nutritional status include eating habits, physical activity, and socioeconomic status. Keywords: body image, fast food, nutritional knowledge, nutritional status